The applications of computerised accounting information systems in the small medium industries: An exploratory study in the northern region / Norasmila Awang…[et al.] - Awang, Norasmila; Abdul Rahman, Nor Hafizah; Hj.Said, Roshima; Wan Omar, Maznah (Research Management Institude, 2004)
Small and Medium Industries (SMIs) serve as a dynamic and integral part of the Malaysian industrial development. In 2003. small medium industries recorded a growth of I 1.8 percent in value added and 8.2 percent in the manufacturing sector. The strategic use of Information and Communication technology within SMIs is seen as one of the key elements that ensure a significant difference in their success. The present study seeks to identify the level of applications of computerized accounting information system in the Small and Medium Industries in the Northern Region. The results showed that 81.6 percent of the SMIs companies have used the computerised accounting systems. LIBS is the most popular software package being used by the companies with the adoption rate of 80.6 percent. The findings indicate that the most favoured modules among the respondents were the general ledger, account payable and receivable and sales and purchases. It is also found that all companies used the module of production planning and scheduling. The rest of the applications such as fixed assets management, inventory control, payroll and costing were moderately used. The types of reports generated by the companies were trading, profit and loss account and balance sheet. Other reports include general ledger, trial balance, income and expenses account, debtors and creditors statement and aging reports, manufacturing account, bank reconciliation, sales and purchases report and fixed asset depreciation.